Solidification and solid-state transformations of metals and alloys - Pero-Sanz Elorz, Jose Antonio (Elsevier, 2017)
Using theoretical formulas to obtain realistic data from industrial operations, this resource includes detailed explanations of chemical, physical and thermodynamic phenomena to allow for a more accessible approach that will appeal to a wider audience. --